Electronic Archiving Systems Used in Higher Education Institutions at University of Basra: a Case Study - Wishah Hamoud, Researcher. Khadija; Hashim Khairi, Prof. Dr. Abdulateef (Basra studies journal, 2023)
The research aims to identify the electronic archiving systems used at university of Basra, as the documentary method was relied on to cover the subject of electronic archiving systems in terms of the concept, requirements, models and characteristics of electronic archiving systems in the theoretical aspect, and the descriptive approach and the analytical method in the practical aspect. The study community consists of (27) units of higher education institutions in Basra university that apply electronic archiving through the analysis of the questionnaire tool distributed to the employees of electronic archiving units amounting as (66) forms. The research reached a set of results, including: 1-- Electronic archiving has been applied in institutions of higher education in the university of Basra by (27) institutions, which constitute (58.6%) of the total educational institutions in the university of Basra, which numbered as (46) educational institutions from the presidencies of universities, colleges, research centers and central libraries. Electronic archiving in some of these institutions and still using traditional archiving, which number (19) institutions, and constitutes (41.3%). 2- The electronic archiving methods that are applied in institutions of higher education at university of Basra differ, including those using the system in the electronic archiving unit, and their number is (13) institutions and constitutes a percentage of (48.1%), while some (12) institutions use the method of folders with a percentage (44.4%), while two institutions use the Access database, with a percentage of (7.5%). As for the recommendations: The research reached a number of recommendations, including: 1- Financial, technical and administrative support must be provided to electronic archiving units in order to advance the reality of archiving and strive to develop work for the better. 2- It is necessary to cooperate with the computer units in order to set up training courses to develop the workers in these units, as well as to update and develop these systems in line with the requirements of the archival work.